Chondrocalcinosis : risk factors and radiographic phenotype - Abhishek, Abhishek (2012)
Objectives: The objectives of this study were to a) examine the distribution of chondrocalcinosis (CC), b) determine the risk factors of CC, and c) examine the radiographic phenotype of osteoarthritis (OA) associated with CC.